The The Application of Virtual Reality to (Mechatronics Engineering) by Creating an Articulated Robotic Work Cell Using EON Reality V9.22.24.24477 - Allaq, Aiman Al-; Jaksic, Nebojsa; Al-Amili, Hussein Ali; Mahmood, Dhuha Mohammed (Al-Khwarizmi Engineering Journal, 2021)
Virtual reality, VR, offers many benefits to technical education, including the delivery of information through multiple active channels, the addressing of different learning styles, and experiential-based learning. This paper presents work performed by the authors to apply VR to engineering education, in three broad project areas: virtual robotic learning, virtual mechatronics laboratory, and a virtual manufacturing platform. The first area provides guided exploration of domains otherwise inaccessible, such as the robotic cell components, robotic kinematics and work envelope. The second promotes mechatronics learning and guidance for new mechatronics engineers when dealing with robots in a safe and interactive manner. And the third provides valuable guidance for industry and robotic based manufacturing, allowing a better view and simulating conditions otherwise inaccessible.